PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LIMIT FUNGSI DI KELAS XI IPA SMA N 1 BUNUT - Morri Manik; Denny Rofika (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
This study aims to improve the learning process and improve learning outcomes by applying the think pair think (TPS) cooperative learning models to class XI science students of SMAN 1 Bunut subject matter Limit Function even semester for the 2016/2017. The low learning outcomes of students of class XI in SMAN 1 Bunut should be suspected because of the lack of student participation, lack of interaction between students and because teachers still tend to use the lecture method in the learning process. This research is a class action research with two cycles. Each cycle consists of two meetings. The research subjects consisted of 24 students. The results showed an improvement in the learning process and an increase in mathematics learning outcomes. Improved learning outcomes can be seen from the results of daily tests I there are 6 students who contributed the development value of 20 and 9 students who contributed the value of development 30. This means that there are 15 students who get a daily test score I is higher than the basic score. In daily test II there were 6 students who contributed 20 developments scores and 14 students who contributed 30 development scores. It means that there were 20 students who got daily II test scores higher than daily test I. Based on the results of this study, it can be concluded that the application of the TPS cooperative learning model can improve the learning process for the better. So that this model may become an alternative model of learning by the teacher when teaching the topic of limit functions.